Fiqh Jihad dan Terorisme (Perspektif Tokoh Ormas Islam Sumatera Utara) - Saidurrahman Saidurrahman (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2012)
Jihad is a teaching and even an obligation to a Muslim. In the Quran, the term jihad is mentioned forty times in sentences. Jihad has an underlying concept for a Muslim life. However, the term jihad is often misconceived, referred to bad things, being violent and even inhumane. Therefore, redefining and restructuring the concept of jihad in Islam is crucial. The province of North Sumatera has often been seen as a terrorist territorial, for many terrorists have been arrested from the province. This has provoked anger for Muslims who are the majority of the population in the province. This is among specific findings of the study, which are based on interviews with the leaders of Muslim organizations in North Sumatera such as al-Jamiyat al-Washliyah, Nahdlatul Ulama, Muhammadiyah, DDII, MMI, DDII, FPI, and MUI.